VASCULAR ACCESS EMERGENCIES IN THE DIALYSIS PATIENT IN NTB PROVINCIAL GENERAL HOSPITAL: A RETROSPECTIVE STUDY: VASCULAR ACCESS EMERGENCIES IN THE DIALYSIS PATIENT IN NTB PROVINCIAL GENERAL HOSPITAL: A RETROSPECTIVE STUDY - Arsatt, Maz Isa Anshori; Hadi, Lalu Rifal (Lombok Health And Science Journal, 2024)
ABSTRACT Background: Hemodialysis (HD) is the most common renal replacement therapy modality in patients with CKD with a prevalence of up to 89%. One method to gain access to hemodialysis quickly is central venous catheterization using a double lumen catheter (CDL). However, the use of temporary CDLs increases the risk of complications such as thrombosis and infection. Currently, data related to CDL in NTB General Hospital is not available in full, both the incidence, germ patterns and antimicrobial sensitivity, causes of CDL emergencies and dysfunction. Researchers are interested in examining the factors that contribute to the incidence of emergency CDL insertion in HD patients at NTB General Hospital. Method: This study was a retrospective observational study. The samples of this study were patients who performed double lumen hemodialysis catheter vascular access measures in the OK CITO room of the NTB Provincial Hospital taken was from January to March 2024. Results and Conclusions: The total sample consisted of 60 (65.9%) males and 31 (34.1%) females. The majority of the samples were from the adult age group with 59 (64.8%) people. The location of CDL insertion was the dextra internal jugular vein 86 (94.5%), sinistra internal jugular vein 3 (3.3%) and femoral vein 2 (2.2%). The most common risk factor indicating CDL insertion was due to CDL detachment 24 (26.4%). it is necessary to recognize the signs of complications from kidney disease so that CDL insertion is carried out immediately as access to hemodialysis. In addition, CDL maintenance is also very required to ensure the smooth delivery of therapy and prevent complications that can complications that may arise from CDL use, especially in patients with long-term use and and to consider the use of other vascular access options. Keywords: HD, CD